2001
DOI: 10.1159/000050968
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Renal Cell Carcinoma Nuclear Grading: Multivariate Analysis of 333 Cases

Abstract: Objective: To evaluate the independent predictive value of the nuclear grading system according to Fuhrman in relation to the disease-specific survival of patients with renal clear cell carcinoma. Material and Methods: 333 patients who underwent radical nephrectomy for renal clear cell carcinoma between 1983 and 1999 were evaluated. In all patients we retrospectively studied nuclear grading, average tumor size, multifocality, pathologic stage of primary tumor, vein invasion, lymph node involvement and distant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 15 publications
2
44
0
4
Order By: Relevance
“…In studies limited to clear cell RCC, where statistical analysis was undertaken, significant differences in survival were demonstrated between all grades or combined grades 1 and 2, grade 3 and 4 tumors. 37,38,40 These data, however, did not always retain significance on multivariate analysis against a variety of staging parameters (local extension nodal and distant metastases). 38,40 In addition, Fuhrman grading has been shown to correlate with outcome for pT1 clear cell RCC, irrespective of tumor size although tumors were grouped (G1 þ G2 vs G3 þ G4) for statistical analysis.…”
Section: Fuhrman Gradingmentioning
confidence: 92%
See 1 more Smart Citation
“…In studies limited to clear cell RCC, where statistical analysis was undertaken, significant differences in survival were demonstrated between all grades or combined grades 1 and 2, grade 3 and 4 tumors. 37,38,40 These data, however, did not always retain significance on multivariate analysis against a variety of staging parameters (local extension nodal and distant metastases). 38,40 In addition, Fuhrman grading has been shown to correlate with outcome for pT1 clear cell RCC, irrespective of tumor size although tumors were grouped (G1 þ G2 vs G3 þ G4) for statistical analysis.…”
Section: Fuhrman Gradingmentioning
confidence: 92%
“…37,38,40 These data, however, did not always retain significance on multivariate analysis against a variety of staging parameters (local extension nodal and distant metastases). 38,40 In addition, Fuhrman grading has been shown to correlate with outcome for pT1 clear cell RCC, irrespective of tumor size although tumors were grouped (G1 þ G2 vs G3 þ G4) for statistical analysis. 42 For papillary RCC there are little data regarding the prognostic significance of Fuhrman grading although in two series grading did not achieve a significant relationship with outcome on multivariate analysis that included tumor stage.…”
Section: Fuhrman Gradingmentioning
confidence: 92%
“…The modified twotiered FG scheme revealed that FG 3-4 patients had a 1.7-fold higher rate of cancer-specific mortality relative to FG 1-2, after adjusting for the effect of all other variables. [17][18][19] In multivariable analyses of discriminant accuracy (Table 3), the multivariable model that included all variables except FG, resulted in 80.3% accuracy. Conversely, the multivariable model that included the conventional four-tiered FG scheme reached 79% accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…20 The stage of the primary, presence of lymphnode invasion, presence of distant metastases, and tumor grade represent examples of established predictors. [17][18][19]21 In renal cell carcinoma, FG represents the most widely used grade stratification scheme. 1 It was endorsed for use in renal cell carcinoma by the Rochester Renal Cell Carcinoma Consensus Conference, with additional endorsement by the College of American Pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly because, as yet, no consensus has been reached on a universal tumor grading system (Kanamaru et al 2001, Medeiros et al 1997. The observed five-year disease-specific survival (DSS) rate is approximately 90% for G1, 70-85% for G2, 45-60% for G3, and 15-30% for G4 (Gudbjartsson et al 2005, Ficarra et al 2001. Currently, different grading systems are utilized at different institutions.…”
Section: Histopathological Tumor Gradingmentioning
confidence: 99%